Knowledge of climate change among students who complete regular basic education in the San Buenaventura district - Rojas Avila, Hector (2021)
The main objective of this research is to investigate the level of knowledge on the subject of climate change among students who are completing regular basic education (EBR) of I.E. José Jaime Heredia Neyra and of I.E. Horacio Zeballos Gámez. The aim was both to corroborate the achievement of the requirements raised in the profile of the graduate of the National Curriculum of the EBR and to identify, through the results, the weaknesses and strengths of students in the area of Social Sciences, since, in them, everything related to environmental issues is studied. First, a test was applied on the contents related to climate, global warming, causes and consequences of climate change; then the information was processed; finally, discussions, conclusions and recommendations were presented.